ROCK1 Mediates Retinal Glial Cell Migration Promoted by Acrolein - Fukutsu, Kanae; Murata, Miyuki; Kikuchi, Kasumi; Yoshida, Shiho; Noda, Kousuke; Ishida, Susumu (Frontiers in Medicine, 2021)
Objective: Acrolein is a highly reactive aldehyde that covalently binds to cellular macromolecules and subsequently modulates cellular function. Our previous study demonstrated that acrolein induces glial cell migration, a pathological hallmark of diabetic retinopathy; however, the detailed cellular mechanism remains unclear. The purpose of this study was to investigate the role of acrolein in retinal glial cell migration by focusing on rho-associated coiled-coil-containing protein kinases (ROCKs). Methods: Immunofluorescence staining for ROCK isoforms was performed using sections of fibrovascular tissue obtained from the eyes of patients with proliferative diabetic retinopathy (PDR). Rat retinal Müller glial cell line, TR-MUL5, was stimulated with acrolein and the levels of ROCK1 were evaluated using real-time PCR and western blotting. Phosphorylation of the myosin-binding subunit of myosin light chain phosphatase [myosin phosphatase target subunit 1, (MYPT1)] and myosin light chain 2 (MLC2) was assessed. The cell migration rate of TR-MUL5 cells exposed to acrolein and/or ripasudil, a non-selective ROCK inhibitor, was measured using the Oris cell migration assay. Results: ROCK isoforms, ROCK1 and ROCK2, were positively stained in the cytosol of glial cells in fibrovascular tissues. In TR-MUL5 cells, the mRNA expression level of Rock1, but not Rock2, was increased following acrolein stimulation. In line with the PCR data, western blotting showed increase in ROCK1 and cleaved ROCK1 protein in TR-MUL5 cells stimulated with acrolein. N-acetylcysteine (NAC) suppressed acrolein-associated Rock1 upregulation in TR-MUL5 cells. Acrolein augmented the phosphorylation of MYPT1 and MLC2 and increased the cell migration rate of TR-MUL5 cells, both of which were abrogated by ripasudil. Conclusions: Our study demonstrated that ROCK1 mediates the migration of retinal glial cells promoted by the unsaturated aldehyde acrolein.